The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13023-021-01998-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived mental health in parents of children with rare congenital surgical diseases: a double ABCX model considering gender

Abstract: Background Previous research has supported the utility of the Double ABCX model of family adaptation for parents in various diseases. Nonetheless, it remains unclear how raising a child with rare congenital surgical diseases impacts the mental health of both mothers and fathers. Methods The potential predictors of maternal and paternal mental health in a German sample of 210 parents of children with rare congenital surgical diseases were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For example, we anticipated that lower family income would be associated with higher stress, anxiety, and depression scores, whereas more physical activity would be associated with have lower stress, anxiety, and depression scores. Given evidence of gender‐specific stress vulnerability (Boettcher et al., 2021 ; Mao & Agyapong, 2021 ) and recent studies suggesting that mothers have been especially impacted by pandemic‐related challenges (Davenport et al., 2020 ; Martucci, 2021 ), we specifically hypothesized that mothers would fare worse than fathers with respect to stress, anxiety, and depression. In addition, consistent with the social determinants model suggesting that the cumulative effects of social risks increase across the lifespan, we hypothesized that there would be stronger relationships between social determinants and anxiety for adolescents compared with younger children.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we anticipated that lower family income would be associated with higher stress, anxiety, and depression scores, whereas more physical activity would be associated with have lower stress, anxiety, and depression scores. Given evidence of gender‐specific stress vulnerability (Boettcher et al., 2021 ; Mao & Agyapong, 2021 ) and recent studies suggesting that mothers have been especially impacted by pandemic‐related challenges (Davenport et al., 2020 ; Martucci, 2021 ), we specifically hypothesized that mothers would fare worse than fathers with respect to stress, anxiety, and depression. In addition, consistent with the social determinants model suggesting that the cumulative effects of social risks increase across the lifespan, we hypothesized that there would be stronger relationships between social determinants and anxiety for adolescents compared with younger children.…”
Section: Introductionmentioning
confidence: 99%
“…Some families of children with EA can adjust and develop a fulfilling life after encountering a medically challenging life event. Others are likely to develop worry, stress, or depressive symptoms in the long term [ 22 , 45 ]. Our study findings would stress the importance of holistic caring support to optimize EA child and family health, especially since it has been shown that there is ample room for improvement to facilitate the pathways to psychosocial care for children with rare diseases and their families [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the finding that for fathers the level of care appears particularly important in assessing the mental health of the healthy sibling is consistent with previous research. 18,19 Although previous research has shown that both children with rare congenital surgical diseases [35][36][37] and their parents 6,7 experience impaired quality of life, future studies should focus primarily on psychosocial factors such as coping mechanisms to identify further relevant predictors of primary outcomes for healthy siblings.…”
Section: Discussionmentioning
confidence: 99%
“…4 One group that seems to be particularly affected by this is families of children with rare chronic diseases. [5][6][7][8] Even though entire families report facing significant care deficiencies and unmet clinical needs due to their diseased child, the siblings of the diseased children appear to be forgotten entirely, especially during the COVID-19 pandemic. 3,9,10 A disease is considered rare in the European Union if it affects less than 5 in 10,000 people.…”
Section: Introductionmentioning
confidence: 99%